Exploring the molecular mechanism of karrikins and strigolactones - Scaffidi, A.; Waters, M.; Bond, C.; Dixon, Kingsley; Smith, S.; Ghisalberti, E.; Flematti, G. (2012)
Karrikins and strigolactones are novel plant growth regulators that contain similar molecular features, but very little is known about how they elicit responses in plants. A tentative molecular mechanism has previously been proposed involving a Michael-type addition for both compounds. Through structure–activity studies with karrikins, we now propose an alternative mechanism for karrikin and strigolactone mode of action that involves hydrolysis of the butenolide ring.